TEACHERS’ PERSPECTIVES ON THE USE OF MOBILE APPLICATIONS FOR LEARNING ENGLISH - Ni’matur , Rohmah; Zulaiha, Siti; Ilyas, Hamzah Puadi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
This study aimed to discover the strategies used by English teachers in online learning using a mobile application and the challenges they face when using it. This research was conducted in a qualitative case study with an open-ended questionnaire and interview. The participants are 16 English vocational high school teachers in Jakarta. It was revealed that most teachers use Google Classroom, Google Forms, Google Meet, and Zoom Meeting. The teachers consider using the application as the optimal method for online English learning. The challenges teachers encounter are the internet network and less supportive devices. The findings of this research can be used as a guide for teaching methods that include mobile applications in teaching-learning activities. The current study is also expected to contribute to stakeholders involved in the education process and to gain the quality of education in the upcoming process while using mobile applications for teaching.